Risk Factors For Sexually Transmitted Infections In Housewives At Telaga Dewa Publichealth Centerbengkulu City In 2025 - Fiya Diniarti; Aprilia Suryadi; Sulastri Diniarti (Journal Hygeia Public Health, 2026)
Sexually Transmitted Infections (STIs) are one of the public health problems that are still commonly found and can have serious impacts on reproductive health. Data obtained at Telaga Dewa Health Center, Bengkulu City, shows that in 2024, 425 patients underwent testing for sexually transmitted infections, with 50 testing positive, and in 2025, 296 people underwent testing, with 64 positive cases. (Telaga Dewa Health Center, Bengkulu City). The purpose to determine the risk factors of sexually transmitted infections in housewives at Telaga Dewa Health Center, Bengkulu City in 2025. The research used in this study is analytical research with a case-control design. The population in this study amounted to 100 respondents, consisting of 50 respondents with sexually transmitted infections (STIs) as the case group and 50 respondents without STIs as the control group. The sampling technique used was total sampling. The types of data used in this study were primary and secondary data. The data analysis used included univariate analysis and bivariate analysis. The statistical test used was the Chi-Square test (χ²), and data processing and analysis were conducted using IBM SPSS Statistics software version 25. Univariate test analysis showed that almost half of the respondents (64.4%) were in the high-risk age group, almost half of the respondents (57.1%) had a secondary education level, half of the respondents (50%) used hormonal contraceptives, and most of the respondents (60%) were married. Almost half of the respondents (55%) had a history of one marriage. Bivariate analysis results showed a significant relationship between age with a p-value of 0.009, education with a p-value of 0.029, contraceptive history with a p-value of 0.000, marital status with a p-value of 0.000, and frequency of marriage with a p-value of 0.000 with the incidence of sexually transmitted infections. Conclusion and Suggestion: There is a relationship between age, education, history of contraceptive use, marital status, frequency of marriage and the incidence of sexually transmitted infections (STIs) in housewives at Telaga Dewa Health Center, Bengkulu City in 2025. Regular screening is recommended for housewives, especially those who have partners with high-risk factors.